Titnago kasimo ir apdirbimo dirbtuvės prie Titno ežero - Šatavičius, Egidijus (Archaeologia Lituana, 2012)
Pastaraisiais dešimtmečiais Pietų Lietuva (Varėnos, Alytaus, Lazdijų rajonai) garsėja miško gėrybėmis (grybais, uogomis) ir ekologija (švariais pušynais bei grynu oru). Tačiau žiloje senovėje – akmens amžiuje – šios vietos buvo garsios kitkuo. Titnago žaliavos gausa – štai kas traukė akmens amžiaus gyventojus visus 12 tūkstančių metų. Iš titnago buvo gaminama dauguma medžioklės, buities ir darbo įrankių, jo trūkumas ar perteklius skatino užmegzti mainus su kitomis bendruomenėmis, kartais net gana tolimomis. Tad kas gi nulėmė šio mineralo gausumą Pietų Lietuvoje?...FLINT MINING SITES AND WORKSHOPS AT LAKE TITNASEgidijus ŠatavičiusSummaryThe Lake Titnas (Citnas) flint mining sites and workshops are at the E end of the Lake Titnas tunnel valley in South Lithuania (Varėna District) and on both sides of the Varėna–Rudnia gravel road and Žvirgždynė stream. In respect to geomorphology, the object is in the contact zone of landscapes with two different origins, i.e. at the juncture of the hilly relief of the ice marginal zone affected by the periglacial processes of the second to last (Medininkai/Warthe) glaciation and the glaciolacustrine plain created by the melting of the last (Nemunas/Weichsel) glacier. Thus the site’s W edge is a sandy plain while the central and E parts are significantly hilly and scored by various ravines (Fig. 1). The flint mining sites and workshops are situated on two of the tunnel valley’s upper terrace treads but isolated finds can also be found at lower sites. During earlier glaciations (probably the Warthe) gigantic cretaceous blocks with abundant flint raw material boulders were transported here and buried. Many places were severely eroded by meltwater during the retreat of the last (Nemunas/Weichsel) glacier, thereby exposing a large number of flint boulders in the neighbouring area. The name, Lake Titnas (dialectically Citnas) probably comes from the abundant surface flint yields. According to the author’s data, only several place/water names in Lithuania are connected with the word, ‘flint’ (Lith. titnagas)....